Daily consumption of growing-up milk is associated with less stunting among Indonesian toddlers (Medical Journal of Indonesia, 2019)
BACKGROUND In Indonesia, animal protein intake in children is low and might contribute to a high prevalence of stunting. This study was aimed to evaluate the association between animal protein source consumption and stunting in toddlers. METHODS This cross-sectional study obtained secondary data from the Ironcheq questionnaire validation study to detect the risk of iron deficiency in toddlers. The Ironcheq study was carried out in five integrated health service posts (Posyandu) in Jakarta from 2013 to 2014. Data from 172 subjects, consisting of 41 stunted (height-for-age z-score less than -2) and 131 normal children, were analyzed to evaluate the association between animal protein source consumption and stunting using multivariate logistic regression test. RESULTS Stunted children tend to come from a family with low parental education and socioeconomic status. Consuming growing-up milk (GUM) ≥300 ml/day was protective against stunting (adjusted OR 0.28, 95% CI 0.13–0.63), whereas consuming red meat product ≥5 times/week was a risk factor (crude OR 3.70, 95% CI 1.17–11.74), however after adjusted to age, sex, and other variables in the questionnaire, the OR was not significant (adjusted OR 3.64 95% CI 1.00–13.26). CONCLUSIONS A daily consumption of 300 ml of GUM may be considered to prevent stunting in toddlers. Red meat products (sausage, nugget, and meatball), which are commonly consumed because of its practicality, could not be considered as significant animal protein sources because of a wide variation of their nutritional content.